HomeSTEAD's physical activity and screen media practices and beliefs survey: Instrument development and integrated conceptual model. - Amber E Vaughn; Derek P Hales; Cody D Neshteruk; Dianne S Ward (PLoS ONE)
The home environment has a significant influence on children's physical activity and obesity risk. Our understanding of this environment is limited by current measurement tools. The Home Self-administered Tool for Environmental assessment of Activity and Diet addresses this gap. This paper describes the development and psychometric testing of its family physical activity and screen media practices and beliefs survey. Methods Survey development was guided by the Analysis Grid for Environments Linked to Obesity (ANGELO) framework and informed by a literature review, expert opinion, and cognitive interviews. Parents of children ages 3-12 years (n = 129) completed the HomeSTEAD survey three times over 12-18 days. Additionally, parents reported on child behaviors and trained staff measured parent and child height and weight. Five exploratory factor analyses were conducted after categorizing items into: control of physical activity, control of screen media, explicit modeling, implicit modeling, and perceived barriers and facilitators. Scales with 3 or more items underwent scale reduction. Psychometric testing evaluated internal consistency (Chronbach's alphas), test-retest reliability (analysis of variance and intraclass correlations (ICC)), and construct validity (correlations with child BMI, physical activity, screen time). An integrated conceptual model of parent physical activity and screen media practices and beliefs was developed based on recent literature to aid in the identification and naming of constructs. Results Final scales demonstrated good internal consistency (median Cronbach's alpha = 0.81, IQR = 0.74-0.85), test-retest reliability (median ICC = 0.70, IQR = 0.66-0.78), and construct validity (with correlations between scale score and children's behaviors generally in the expected direction). Comparison with the integrated conceptual model showed that most identified constructs were captured. Conclusions The family physical activity and screen media practices survey advances the measurement of the home environment related to children's physical activity, screen time, and weight. The integrated conceptual model provides a useful framework for researchers studying both physical activity and screen media parenting practices.